The Three-Cornered Alfalfa Hopper, Spissistilus festinus, Is a Vector of Grapevine Red Blotch Virus in Vineyards - Flasco, Madison T.; Hoyle, Victoria; Cieniewicz, Elizabeth J.; Loeb, Greg; McLane, Heather; Perry, Keith; Fuchs, Marc F. (Viruses, 2023)
Spissistilus festinus (Hemiptera: Membracidae) transmit grapevine red blotch virus (GRBV, Grablovirus, Geminiviridae) in greenhouse settings; however, their role as a vector of GRBV in vineyards is unknown. Following controlled exposures of aviruliferous S. festinus for two weeks on infected, asymptomatic vines in a California vineyard in June and a 48 h gut clearing on alfalfa, a nonhost of GRBV, approximately half of the released insects tested positive for GRBV (45%, 46 of 102), including in the salivary glands of dissected individuals (11%, 3 of 27), indicating acquisition. Following controlled exposures of viruliferous S. festinus for two to six weeks on GRBV-negative vines in vineyards in California and New York in June, transmission of GRBV was detected when two S. festinus were restricted to a single leaf (3%, 2 of 62 in California; 10%, 5 of 50 in New York) but not with cohorts of 10–20 specimens on entire or half shoots. This work was consistent with greenhouse assays in which transmission was most successful with S. festinus exposed to a single leaf (42%, 5 of 12), but rarely occurred on half shoots (8%, 1 of 13), and never on entire shoots (0%, 0 of 18), documenting that the transmission of GRBV is facilitated through the feeding of fewer S. festinus on a restricted area of grapevine tissue. This work demonstrates S. festinus is a GRBV vector of epidemiological importance in vineyards.